2021
DOI: 10.1016/j.energy.2020.119112
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the effects of nanoparticles and stair fins on performance improvement of phase change thermal energy storages

Abstract: Using nano-enhanced phase change materials is a widespread passive method to improve the melting performance, and also the storage capacity of the thermal energy storage units. In this study, the effects of CuO nanoparticles  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…They noted that employing downward stepped fins instead of conventional horizontal fins can achieve improvements of up to 65.5% in the melting process. Additionally, Nakhchi et al 17 numerically investigated the addition of conductive nanoparticles alongside stepped fins, with results showing enhanced energy storage capacities that reach a maximum of 474.1 kJ for a stair ratio of 4 and volume concentration of 1.5%. Yang et al 18 investigated the performance of metal foams in melting of PCMs with positive and negative gradient designs in pore parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that employing downward stepped fins instead of conventional horizontal fins can achieve improvements of up to 65.5% in the melting process. Additionally, Nakhchi et al 17 numerically investigated the addition of conductive nanoparticles alongside stepped fins, with results showing enhanced energy storage capacities that reach a maximum of 474.1 kJ for a stair ratio of 4 and volume concentration of 1.5%. Yang et al 18 investigated the performance of metal foams in melting of PCMs with positive and negative gradient designs in pore parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al [3] used the calculation of the fin efficiency of a serrated type of finned surface for more complicated research on the air-water heat exchanger for the data center. Nakhchi et al [4] used the calculation of the effectiveness of stepped fins' area on the performance improvement of phase change thermal energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…The available studies in the literature have reported that combining heat transfer enhancement techniques can lead to a better heat transfer performance of the storage unit [22,23]. Studies can be found using a combination of fins and heat pipes [24], nanoparticles and fins [25,26], nanoparticles and metal foams [27], metal foams, and heat pipes [28]. Ren et al [29] studied the application of triangular fins in a rectangular LHTES with and without the presence of nanoparticles in the PCM.…”
Section: Introductionmentioning
confidence: 99%